Fentanyl vs fentanyl-dexmedetomidine in lumbar foraminotomy surgery - Abdul Hadi B; Sbeitan SM; Shakya AK (Dove Medical Press, 2019)
Bushra Abdul Hadi,1 Saleh M Sbeitan,2 Ashok K Shakya11Faculty of Pharmacy and Medical Sciences, Al-Ahliyya Amman University, Amman 19328, Jordan; 2Intensive Care Unit, Specialty Hospital, Amman 19328, JordanAim: Lumbar foraminotomy surgery requires a potent opioid with short duration and rapid onset of action. In the present study we intended to compare the efficacy of fentanyl alone vs the combination of dexmedetomidine and fentanyl during lumbar foraminotomy surgery.Methods: The duration and requirements for first postoperative analgesics, hemodynamic stability, and respective side effects were studied. A prospective, randomized, double blind study of 40 patients (fentanyl group [Fen group] and fentanyl-dexmedetomidine group [Fen-Dex group], n=20 each) scheduled for lumbar foraminotomy surgery under pharmaceutical care intervention was carried out. Patients were classified as class I or II, according to the American Society of Anesthesiologists physical status classification. Patients received intraoperative propofol, sevoflurane, atracurium, and either fentanyl loading dose of 1.0 μg/kg and maintenance infusion dose of 0.2 μg/kg/h in both groups. The patients of the Fen group received normal saline (0.9%) placebo, while the patients of the Fen-Dex group received dexmedetomidine infusion (0.5 μg/kg/h) along with the fentanyl infusion. Postoperative morphine doses were given. Hemodynamic stability, pain, postoperative analgesia requirement, side effects of drugs, and other effects were monitored.Results: In the Fen-Dex group, the pain score was significantly less than in the Fen group (p<0.05). The time to first postoperative analgesia request was prolonged in the Fen-Dex group compared to the Fen group. On the other hand, requirement of morphine, and postoperative symptoms and episodes of nausea and vomiting were significantly greater in the Fen group than in the Fen-Dex group (p<0.05).Conclusion: The present study suggests the addition of dexmedetomidine during lumbar foraminotomy surgery at different levels would be beneficial to reduce morphine consumption and any adverse drug reaction.Keywords: dexmedetomidine, foraminotomy surgery, fentanyl, postoperative analgesics, hemodynamic stability, adverse drug reactions